Philosophy and Leadership: An Evolution of Leadership from Ancient Times to the Digital Age - Łukasz Sułkowski; Zdzisława Dacko-Pikiewicz; Katarzyna Szczepańska Woszczyna (Routledge, 2024)
Philosophy and Leadership is an ambitious exploration of leadership's philosophical underpinnings from antiquity to the AI-driven future. The book journeys through history, gleaning insights from eminent philosophers and contextualizing their teachings to leadership. The book's foundational premise lies in the symbiosis of philosophy and leadership. Philosophy provides the "why""that drives the practices and decisions in leadership. This intricate connection is unfolded from the teachings of Confucius on virtue and ethics to the contemporary dialogues of Judith Butler on leadership identity. The book also delves into the evolution of leadership concepts through various eras—medieval times highlighting religious and scholastic perspectives, the Renaissance juxtaposing Machiavellian pragmatism with More's utopian ideals, and the Enlightenment era underscoring the importance of duty, skepticism, and rationality. An exciting aspect of the narrative is the amalgamation of evolution and leadership. By drawing parallels between Darwin's natural selection and leadership dynamics or Bergson's vitalism and intuitive leadership, the authors present a merger of biological evolution with leadership's ever-evolving paradigms. Finally, the concluding chapters reside in envisioning the future and reflect upon the impending synergy between AI and leadership. They emphasize the importance of amalgamating philosophical wisdom with the promises and challenges brought about by AI. The book will guide readers from the philosophical epochs of yore to the AI-predicted leadership paradigms of the future. By intertwining the enduring wisdom of philosophers with the dynamic nature of leadership, this book serves as a beacon for anyone aspiring to lead in any era.
Keywords: 650; Philosophy of Leadership; Leadership Dynamics; Historical Evolution; Ancient Eastern Philosophy; Ethical Decision-making; Renaissance; Enlightenment; Contemporary Leadership